Unravelling risk factors in Turkish wheat in a changing global landscape - Huseyin Tayyar Guldal; Ozdal Koksal; Osman Orkan Ozer; Onur Terzi; Erdogan Gunes; Aysegul Selisik (Agricultural Economics (AGRICECON))
This study comprehensively examines multifaceted risk factors influencing wheat production among Turkish farmers, aiming to deepen understanding of how these factors shape farmers' perceptions and decision-making processes. Utilising Structural Equation Modeling (SEM), we analysed the interplay of climate-related issues (F1), market dynamics (F2), and external events (F3), like COVID-19 and wars, alongside socio-demographic factors such as education, income, and land ownership. Findings revealed that higher education and increased agricultural income reduced price-related risks while expanding wheat cultivation areas heightened risk perceptions. Farmers in irrigated regions prioritised cyclical risks, whereas those in dry areas perceived climatic risks as more severe. Capital-intensive practices and storage facilities mitigate climate change and market variability risks, with committed wheat producers showing lower climate change risk perceptions. External factors like the Russian-Ukrainian war and the COVID-19 pandemic disproportionately impact irrigated area farmers. This study contributes to the existing literature by using empirical evidence from Turkish wheat farming to explore diverse risk perceptions, employing SEM to unravel complex risk factors and decision-making processes, thereby offering new insights for future agricultural risk management research.